2022
DOI: 10.1021/acs.inorgchem.1c03144
|View full text |Cite
|
Sign up to set email alerts
|

Lead Tellurite Crystals BaPbTe2O6 and PbVTeO5F with Large Nonlinear-/Linear-Optical Responses due to Active Lone Pairs and Distorted Octahedra

Abstract: The exploration of nonlinear-/linear-optical crystal materials with high performance is an extremely difficult research project. Herein, the two new lead tellurite crystals BaPbTe 2 O 6 and PbVTeO 5 F were successfully obtained through a facile hydrothermal synthesis strategy. BaPbTe 2 O 6 lies in the noncentrosymmetric (NCS) and chiral orthorhombic space group P2 1 2 1 2 1 , featuring a unique ∞ 1 [PbTe 2 O 6 ] chain consisting of the PbO 4 and TeO 3 building units, while PbVTeO 5 F belonging to the centrosym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…The IR spectra for both compounds revealed that they have similar IR absorptions. The bands attributed to the Te–O vibrations over the range of 400–780 cm –1 are in good agreement with the reported tellurites. , More absorption bands are observed than in regular metal tetrafluoroborates as a result of the disordered BF 4 – anion’s reduced symmetry, and the absorption bands in the lower wavenumber range are more complex due to the interaction of tellurites and tetrafluoroborates’ vibrations. The absorptions at 1086 and 1056 cm –1 for compound 1 and 1076 and 1023 cm –1 for compound 2 may be attributed to the vibrations of B–F bonds in both compounds .…”
Section: Resultssupporting
confidence: 85%
“…The IR spectra for both compounds revealed that they have similar IR absorptions. The bands attributed to the Te–O vibrations over the range of 400–780 cm –1 are in good agreement with the reported tellurites. , More absorption bands are observed than in regular metal tetrafluoroborates as a result of the disordered BF 4 – anion’s reduced symmetry, and the absorption bands in the lower wavenumber range are more complex due to the interaction of tellurites and tetrafluoroborates’ vibrations. The absorptions at 1086 and 1056 cm –1 for compound 1 and 1076 and 1023 cm –1 for compound 2 may be attributed to the vibrations of B–F bonds in both compounds .…”
Section: Resultssupporting
confidence: 85%
“…30 The stereochemically active lone-pair electrons of Te IV cations are generally beneficial for improving the birefringence of materials. Some recent literature studies have proven this, such as PbVTeO 5 F (0.142 at 590 nm; 2.22 eV), 31 Bi 4 TeO 4 F 4 (TeO 3 ) 2 (SeO 3 ) 2 (0.20 at 1064 nm; 2.74 eV), 28b and HgTeO 2 F(OH) (0.09 at 1064 nm; 3.26 eV). 29 However, many of the reported tellurites exhibit small band gaps, which greatly hamper their availability in the field of birefringent materials.…”
mentioning
confidence: 76%
“…The stereochemically active lone-pair electrons of Te IV cations are generally beneficial for improving the birefringence of materials. Some recent literature studies have proven this, such as PbVTeO 5 F (0.142 at 590 nm; 2.22 eV), Bi 4 TeO 4 F 4 (TeO 3 ) 2 (SeO 3 ) 2 (0.20 at 1064 nm; 2.74 eV), and HgTeO 2 F­(OH) (0.09 at 1064 nm; 3.26 eV) . However, many of the reported tellurites exhibit small band gaps, which greatly hamper their availability in the field of birefringent materials. , In order to improve the band gap of tellurite birefringent materials, the researchers have attempted the following and made progress: (1) introducing tetrahedral anionic groups with a wide transmission range, such as Y 2 (Te 4 O 10 )­(SO 4 ) (0.124 at 1064 nm; 4.1 eV) and Ba 2 TeP 2 O 9 (0.126 at 1064 nm; 4.28 eV), (2) introducing the strongest electronegative F element, such as BaF 2 TeF 2 (OH) 2 (0.078 at 300–700 nm; 5.9 eV) and Li 7 (TeO 3 ) 3 F (0.097 at 1064 nm; 4.75 eV), and (3) introducing planar triangular groups, , such as LaTeBO 5 (0.083 at 532 nm; 4.2 eV) …”
mentioning
confidence: 95%
“…These assignments correspond to the reported tellurites. 52,[58][59][60][61][62][63] The UV-vis-NIR diffuse-reflectance spectra of the three compounds show that they have no obvious absorption in the range of 500-2000 nm (Fig. 6).…”
Section: Ir and Uv-vis-nir Spectramentioning
confidence: 99%